(untitled) (Journal of Agriculture & Rural Development, 2008)
The study was undertaken with a view to investigate the effects of different basal media and organic extracts on organogenesis of Dendrobium orchid. Protocorm like bodies (PLBs) were cultured in Knudson C (KC), Vacin and Went (VW), half strength Murashige and Skoog (½MS) and New Phalaenopsis (NP) media supplemented with Sabri banana pulp (Sb), Charcoal (C) and Coconut water (Cw) organic extracts. KC, VW, ½MS and NP media significantly influenced the plantlet regeneration of Dendrobium orchid. Among the media, ½MS showed better performance on fresh weight, number PLBs, shoots and leaves per plantlet, The longest shoots were found in KC medium and maximum length of leaves was found in both KC and ½MS media. In case of different organic extracts Sb showed significantly better performance on fresh weights of PLBs, number of shoot and leaves per explant, length of shoots and leaves. Key words: Organogenesis, Dendrobium, media, organic extracts. DOI = 10.3329/jard.v5i1.1454 J Agric Rural Dev 5(1&2), 30-35, June 2007